1998
DOI: 10.1172/jci2749
|View full text |Cite
|
Sign up to set email alerts
|

A novel epitope on the C-terminus of SmD1 is recognized by the majority of sera from patients with systemic lupus erythematosus.

Abstract: The SmD1 protein is a specific target for the autoantibody response in SLE. To further analyze this reactivity epitope, mapping was performed with cellulose-bound 13-mer peptides overlapping 10 amino acids (aa). In this initial approach, 4 out of 15 SLE sera recognized more than five overlapping peptides of the SmD1 C-terminus. Therefore, longer oligopeptides of up to 37 aa of this region were generated and probed for as antigens by ELISA. For the SmD1 aa 83-119 polypeptide, there was a striking increase of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
2
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 36 publications
8
105
2
5
Order By: Relevance
“…An additional group has shown that this same region of Sm D1 is antigenic when the alternating arginines are dimethylated (35). Interestingly, this posttranslational modification may not be absolutely required for antigenicity of these sequences, as has been shown by this and other works (8,(33)(34). Additional experiments are underway to understand the overall importance of symmetrical dimethylation of these sequences with regard to lupus autoimmunity.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…An additional group has shown that this same region of Sm D1 is antigenic when the alternating arginines are dimethylated (35). Interestingly, this posttranslational modification may not be absolutely required for antigenicity of these sequences, as has been shown by this and other works (8,(33)(34). Additional experiments are underway to understand the overall importance of symmetrical dimethylation of these sequences with regard to lupus autoimmunity.…”
Section: Discussionmentioning
confidence: 77%
“…This carboxyl-terminal region of Sm D1 has been determined by several investigators to be the major target of the human and murine lupus anti-Sm D1 response (10 -14, 29 -30, 33). Immunization with this C-terminal D1 peptide causes lupus-like disease in rabbits as well as the production of anti-D1 and anti-D3 autoantibodies (33) and accelerates disease in lupus-prone animals (New Zealand Black/White mice) (34). The data from the (GR)-repeat portion of the D3 polypeptide, its similarity to D1, and the cross-reactivity of affinity-purified anti-D3 Abs with this region of D1 seem to support the theory of crossreactivity explaining the appearance of some autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ELISA using components of Sm/RNP demonstrated that Vκ38C + antibodies strongly react to the glycine-arginine-rich C-terminal part (residues 83-119) of SmD1 (Fig. S2), the major epitope recognized by anti-Sm antibodies from SLE patients (24,25). Thus, Vκ38C + antibodies show antigen specificity similar to anti-Sm antibodies in SLE, although 56R/Vκ38C + are potentially reactive to other self-antigens (26).…”
Section: Cd40mentioning
confidence: 93%
“…n systemic lupus erythematosus (SLE), 4 a typical systemic autoimmune disease, high affinity Abs to several autoantigens, such as dsDNA, nucleosomes, and Smith (Sm) proteins, specifically occur and lead to tissue damage (1)(2)(3). These autoantibodies, which belong to the normal repertoire of autoantibodies in healthy individuals, require T cell help for their production as IgG.…”
mentioning
confidence: 99%